2008
DOI: 10.1289/ehp.11064
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of Perfluorinated Compounds in Children and Adults Exposed to Perfluorooctanoate-Contaminated Drinking Water

Abstract: Objective40,000 residents in Arnsberg, Germany, had been exposed to drinking water contaminated with perfluorinated compounds (PFCs). Internal exposure of the residents of Arnsberg to six PFCs was assessed in comparison with reference areas.Design and participantsOne hundred seventy children (5–6 years of age), 317 mothers (23–49 years), and 204 men (18–69 years) took part in the cross-sectional study.MeasurementsIndividual consumption of drinking water and personal characteristics were assessed by questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
181
2
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(198 citation statements)
references
References 26 publications
10
181
2
4
Order By: Relevance
“…PFOA, instead of PFOS, was the dominant analyte (Pan et al, 2010;Guo et al, 2011). Consistent with other studies, the univariate analysis showed that concentrations of PFOA, PFNA and PFOS were significantly correlated with age, and concentrations of PFOA, PFNA, PFDA and PFOS appeared to be higher in males than those in females (Calafat et al, 2007;Fromme et al, 2007;Holzer et al, 2008;Haug et al, 2009;Zhang et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…PFOA, instead of PFOS, was the dominant analyte (Pan et al, 2010;Guo et al, 2011). Consistent with other studies, the univariate analysis showed that concentrations of PFOA, PFNA and PFOS were significantly correlated with age, and concentrations of PFOA, PFNA, PFDA and PFOS appeared to be higher in males than those in females (Calafat et al, 2007;Fromme et al, 2007;Holzer et al, 2008;Haug et al, 2009;Zhang et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…Water source was the primary determinant of serum PFOA concentrations (Emmett et al, 2006). Biomonitoring data showed 4-8 fold higher PFCs concentrations in blood plasma of population exposed to PFCs contaminated drinking water compared with controls (Holzer et al, 2008). These can also explain why the concentrations of PFOS and PFOA in this study were much lower than concentrations from developed countries like USA (Nelson et al, 2010), Japan (Harada et al, 2010) and Germany (Fromme et al, 2009), only higher than those reported for South Africa (Hanssen et al, 2010) and Peru (Calafat et al, 2006b).…”
mentioning
confidence: 50%
“…Significant correlations of serum PFCs with age were reported in some studies (Holzer et al, 2008;Haug et al, 2009;Zhang et al, 2010b). In a Chinese study, the concentration of PFOS increased significantly with age, while PFOA concentration showed a negative correlation with age (Zhang et al, 2010b).…”
Section: Age Effect On Pfcs Concentrationsmentioning
confidence: 89%
See 1 more Smart Citation
“…Gehalte im Blut gemessen als in unbelasteten Vergleichskollektiven [18]. Nach Reduzierung der PFC-Kontamination des Trinkwassers durch Aktivkohlefiltration sowie Verminderung des weiteren Eintrags von PFC in die Oberflächengewässer zeigte sich bei Wiederholungsmessungen im Jahr 2012 ein Rückgang der PFOA-Belastung um 75 % im geometrischen Mittel [19].…”
Section: Eintragspfade Von Pfc In Die Umweltunclassified